Coplanar Wave Guide Fed Dual Band Notched MIMO Antenna - D S Ramkiran; B T P Madhav; Kankara Narasimha Reddy; Shaik Shabbeer; Priyanshi Jain; Saggurthi Sowmya (International Journal of Electrical and Computer Engineering (IJECE), 2016)
A coplanar wave guide fed of semicircle monopole antenna is designed in this work to overcome polarization diversity mimo technique is implemented in this paper. The proposed antenna is designed to notch a particular band of frequencies in UWB range. The designed model is notching the first band from 2 to 5 GHz & the second band from 7 to 11 GHz. The proposed antenna has been fabricated on FR4 substrate with di electric constant 4.4 & tested for its reliability on ZNB20 vector network analyzer. The operating bands will come under WLAN, KU band, satellite communication applications. A peak realized gain of 4.3 dB with radiation efficiency 90% is attained at the operating bands of the designed antenna. At notch band significant gain reduction is observed from the current design. The antenna is showing omnidirectional radiation pattern in the pass band & disturbed radiation pattern in the notch band. Antenna is fabricated with dimensions of 40x68x1.6 mm & simulation works are carried with finite element method based HFSS tool.